2010
DOI: 10.1186/1746-1596-5-23
|View full text |Cite
|
Sign up to set email alerts
|

A comparability study of 5 commercial KRAS tests

Abstract: BackgroundActivating mutations in the KRAS gene occur frequently in human tumors, including colorectal carcinomas; most mutations occur in codons 12 and 13. Mutations in KRAS have been associated with poor response to anti-epidermal growth factor receptor antibodies. Therefore, an accurate and readily available analysis of KRAS mutational status is needed. The aim of this study was to evaluate concordance between KRAS assays performed by 6 different laboratories.MethodsForty formalin-fixed paraffin-embedded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…However, in a separate comparability study, we found assessment of KRAS status using Roche 454 pyrosequencing to have a high level of agreement (k ¼ 0.94) with direct sequencing (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a separate comparability study, we found assessment of KRAS status using Roche 454 pyrosequencing to have a high level of agreement (k ¼ 0.94) with direct sequencing (20).…”
Section: Discussionmentioning
confidence: 99%
“…The multigene sequencing assays were extensively qualified to show the ability to confidently detect mutations at a level of 5% of sequence reads per amplicon using both cell line DNA and procured FFPE colorectal tumor samples. Because of the nature of this qualification, the demonstration of correlation between this sequencing methodology and bidirectional sequencing (20), the lack of commercially available validated assays for all of these mutations and the limiting amount of material available for these samples, confirmation of the mutation status using an additional method was not pursued.…”
Section: Translational Relevancementioning
confidence: 99%
“…All four of them reported discordance in some cases. As for the reliability of the other techniques used in the studies reported in Table 1, a paper by Oliner et al [64], evaluating five different KRAS tests, showed that classic DNA sequencing as well as pyrosequencing and AS-PCR provide accurate KRAS analysis. The commercial ASO kit described in that paper was reported to be less accurate.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are characterized by different sensitivity, turnaround time, and cost. [12][13][14][15] Besides the use of robust KRAS testing methods, the selection of the appropriate tissue to be tested is also critical. Particularly, evaluation of the tumor cellularity is essential to guide the interpretation of the molecular data.…”
mentioning
confidence: 99%